(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
Phase separation in the nonionic surfactant solutions at the presence of hydrotropic additions, electrolyte and ionic surfactant sodium dodecylsulphate was investigated. The influence of the concentration conditions, addition of electrolytes, anionic surfactant and phenol on the phase separation of OP-7 water solutions was studied.